Implementing the dynamic simulation approach for the design and optimization of ships energy systems: Methodology and applicability to modern cruise ships. (October 2021) - Barone, G.; Buonomano, A.; Forzano, C.; Palombo, A.
Abstract: To reduce the environmental impact of modern cruise ships, a crucial role is played by the recovery of waste heat from onboard diesel generators used to balance part of the onboard thermal energy demand. To maximize the recovered waste heat, this paper proposes a novel design methodology for ships energy systems based on the dynamic simulation approach, suitably enhanced to consider moving objects like ships. Through this approach, partial load regimes due to variable energy requirements and the relative response of innovative energy saving technologies are dynamically assessed by properly considering real cruising conditions as a function of the current ship position along its route. To this aim, 3-D ship envelope models, detailed energy ship-plant system layouts, and algorithms for deriving new customized hourly weather data files are suitably developed in MatLab and TRNSYS. To show the capability and potentials of the proposed methodology, a novel case study referred to an LNG-powered cruise ship traveling in the Norwegian fjords sea is presented. Different thermally and electrically activated technologies are coupled in 16 energy ship-plant system layouts, implementing novel controls strategies for optimizing the exploitation of the waste heat recoveries and cold-ironing. Encouraging results are achieved for the best layout, including primary energy savings of 18.1%, avoided pollutants emissions of 24.4 ktCO2 /y, 40.0 tNOx /y, 90.0 tSOx /y, 84.0 tPM2.5 /y, and a simple payback of 0.68 years. Finally, the proposed methodology represents a step forward toward the modern early design of onboard ship energy systems useful for ship designers, manufacturers, owners and operators. Highlights: Dynamic energy simulations for modern cruise ships sailing in cold seas. A novel approach for sustainable design of energy ship plant system layouts. Waste heat recovery of high, medium, and low temperatures from LNG engines. Sixteen different system layouts implementing innovative technology are simulated. Energy, economic and environmental assessment of cold ironing strategy.